Clinical simulation in teaching Pediatric Nursing: students’ perception - Mayara Gombrade Teles; Ana Márcia Chiaradia Mendes-Castillo; Ana Railka de Souza Oliveira-Kumakura; Juliany Lino Gomes Silva (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to comprehend the perception of undergraduate nursing students about learning to care for the child and family through clinical simulation. Methods: this is a qualitative research conducted with ten nursing students through semi-structured interviews. Data were analyzed through content analysis. Results: data were organized into two categories: “learning a new way to learn,” in which students describe their experiences during the simulation, and “learning a new way to care,” in which they reflect on learning through simulation. Final considerations: we believe that clinical simulation practice in teaching should be encouraged because of the benefits it can offer to the students, faculty, patients and their families. However, we recommend further studies to validate scenarios of child and family healthcare.